Approximation of (ψ, β)-differentiable functions of low smoothness by biharmonic Poisson integrals - Zhyhallo, K. M.; Kharkevych, Yu. I.; Жигалло, К. М.; Харкевич, Ю. І. (Institute of Mathematics, NAS of Ukraine, 2011)
We solve the Kolmogorov – Nikol’skii problem for biharmonic Poisson integrals on the classes of (ψ, β)- differentiable periodic functions of low smoothness in the uniform metric.